Influence of sowing time on grain yield of amaranth of the Western Forest-Steppe of Ukraine - Tyrus, M. (Scientific Progress & Innovations, 2023)
Amaranth is an ancient pseudocereal crop, the potential of which has not yet been realized. We can say that currently amaranth is being discovered "anew". It is widely used in the food, pharmaceutical, and cosmetic industries. Amaranth is a niche crop in Ukraine with small cultivated areas, the crops are mainly concentrated in the East and South. The timing of sowing for amaranth is an important technological factor in realizing the level of productivity, which affects the timely receipt of seedlings and the duration of the growing season, especially when growing it for seeds. Field research was conducted in the conditions of the Western Forest-Steppe at the experimental field of the Department of Technologies in Crop Production of the Lviv National University of Nature Management on a dark gray podzolized light loamy soil. Hydrothermal conditions in the years of research differed slightly from the average long-term data, but, in general, were favorable for growing amaranth. The total area of the plot was 30 m2, accounting – 20 m2. Research was carried out in three repetitions. The seed sowing rate was 0.4 million/ha for mineral fertilizer rates N160P60K120. In the researches, the mid-ripening Lyera variety (A. hypochondriacus) was used, the protein content in the seeds was 20.6 %, the oil content was 7.0 %, and the seed yield was up to 22 t/ha. Amaranth belongs to heat-loving plants. To obtain friendly seedlings, the soil should warm up to 8–10 °С. Research has established that only by sowing at the optimal time, plants can fully use all the necessary factors for their growth and development and the formation of the highest yield. Field germination (76 %), plant density (30 units/m2) of amaranth in the seedling phase, plant survival during the growing season (88–90 %) and plant density before harvest (26–27 units/m2) were highest for sowing in the summer months . The mass of seeds per plant (21 g), on which the level of productivity depended the most, was the largest for sowing on April 30. The optimal time for sowing amaranth of the Lyera variety in the conditions of the western forest-steppe of Ukraine is April 30. Valid dates are in the range from April 15 to May 15. Sowing amaranth in the summer months is advisable only when growing for green mass.